Maternal and neonatal outcome in pregnancy with previous lower segment caesarean section undergoing trial of scar - Dalal, Monika; Nanda, Smiti; Dalal, Jagjit S.; Kaushik, Samiksha; Chauhan, Meenakshi; Malhotra, Vani; Chaudhary, Sushila; Rani, Vandana; Singh, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Women with previous LSCS often have to make a decision about mode of delivery of their second baby. As the rate of caesarean section is continuously increasing, vaginal birth after caesarean section (VBAC) is a good strategy to decrease caesarean rate. The present study was planned to assess the fetomaternal outcome in pregnancies with previous lower segment caesarean section undergoing trial of scar and to identify the factors, which can influence the outcome of trial of scar. Methods: This was a prospective observational study on 100 patients at a tertiary care institute. Pregnant women with previous LSCS were selected randomly for the study on the basis of the inclusion and exclusion criteria. Each labor monitored closely using a partogram. Decision for repeat emergency caesarean was taken by consultant. All women included in the study were followed through delivery and till discharge. Results: Out of 100 pregnant women 49 % cases had successful VBAC, 50% had emergency caesarean and one patient had laparotomy for rupture uterus. In women, who also had a prior vaginal delivery, 72% delivered vaginally, as compared to 40% of the women who did not undergo prior vaginal delivery (p value=0.003). Women who were in spontaneous labor, 59.21% delivered vaginally, whereas women who were induced, 16.6% delivered vaginally. The rate of perinatal complication was more in the patients who required an emergency CS after a failed trial. Conclusions: Our findings may encourage obstetricians to encourage VBAC in the properly screened ANC patients and decrease the rate of recommending caesarean section.